Rekontruksi Sumber Daya Manusia Sebagai Upaya Meminimalkan Resiko Operasional Perbankan (Studi Literasi Teori Motivasi) - M Soleh Mauludin; Soimah, Zakiyatus (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
The research aims to analyze the causes of operational risks in Islamic banking, as well as ways to overcome them. Using qualitative research and Maslow's motivation theory, this study concluded that human resources in Islamic banking come from various educational backgrounds. On the other hand, Islamic banking must also be able to manage its human resources so that it does not cause operational risks. So that these operational risks do not arise, it is necessary to reconstruct human resources by increasing the motivation of human resources.